ELABORATION D'UNE BASE GEOGRAPHIQUE D'UN SYSTEME D'INFORMATION A REFERENCE SPATIALE./(THE SETTING UP OF A GEOGRAPHICAL BASE FOR AN URBAN AND REGIONAL INFORMATION SYSTEM). - Rivard, Bertrand J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF